Pengaruh Temperatur Penumbuhan Terhadap Karakteristik Magnetik Film Tipis TiO2:Co yang ditumbuhkan dengan Metode Metalorganic Chemical Vapor Deposition (MOCVD) - Horasdia Saragih; Pepen Arifin; Moehamad Barmawi; Mersi Kurniati (Institut Teknologi Bandung, 2004)
TiO2:Co thin films have been grown on p-type Si(100) substrates by MOCVD method. The films were grown at substrate temperature of 450 oC to 500 oC , and the temperature of precursor bubbler was kept constant at 50 oC with vapor pressure of 260 Torr. Flow rate of O2 and Ar are 60 sccm and 100 sccm, respectively. The crystal structure, grain shape and magnetic properties of the films depend significantly on the substrate temperature. The anatase-213 structure with columnar grain was formed for the films grown at temperatures of 400 oC and 450 oC. The arrangement of atoms at grain boundary is improved at growth temperature of 450 oC. Anatase-301 structure with cone grain shape as additional component appears at growth temperature of 500 oC. The TiCoO3 phase with 310 plane was found at growth temperature of 550 oC. The grains grow at direction of -45o from normal substrate. Films that grown at 450 oCand 500 oC exhibit soft magnetic properties with Hc of 100 Oe and 80 Oe; and Mr of 250 emu/cm3 and 220 emu/cm3, respectively. The hard magnetic properties of the films are shown for the films grown at 550 oC. The films were grown for 2 hours producing the films with thickness of about 0.7 to 0.9 Î¼m.